Stereo-controlled approach to pyrrolidine iminosugar C-glycosides and 1,4-dideoxy-1,4-imino-L-allitol using a D-mannose-derived cyclic nitrone - Bande, Omprakash P.; Jadhav, Vrushali H.; Puranik, Vedavati G.; Dhavale, Dilip D.; Lombardo, Marco (Tetrahedron Letters, 2009)
Intramolecular N-alkylation of 2,3-O-isopropylidene-5-O-methanesulfonyl-6-O-t-butyldimethylsilyl-D-mann ofuranose-oxime 7 afforded a five-membered cyclic nitrone 9, which on N-O bond reductive cleavage followed by deprotection of -OTBS and acetonide functionalities gave 1,4-dideoxy-1,4-imino-L-allitol (DIA) 3. Addition of allylmagnesium chloride to nitrone 9 afforded alpha-allylated product 10a in high diastereoselectivity providing an easy entry to N-hydroxy-C1-alpha-allyl-substituted pyrrolidine iminosugar 4a after removal of protecting group, while N-O bond reductive cleavage in 10a afforded C1-alpha-allyl-pyrrolidine iminosugar 4b. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cyclic nitrone; Enzyme inhibitors; Iminosugars; pyrrolidine